Revisiting the regional growth convergence debate in Colombia using income indicators - Boris Branisa; Adriana Cardozo (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
This paper investigates growth convergence across Colombian departments during the period of 1975 to 2000, following both the regression and the distributional approaches suggested in the literature, and using two income measures computed by Centro de Estudios Ganaderos (CEGA).We also discuss issues related to data provided by Departamento Administrativo Nacional de Estadisticas (DANE) used by previous convergence studies. Our results show no evidence supporting convergence using per capita gross departmental product, but rather persistence in the distribution. Using per capita gross household disposable income, we find convergence, but only at a low speed, close to one percent per year. Furthermore, we find no evidence of the existence of different steady states for the two variables considered.
Keywords: C11; O40; O54; 330; Colombia; regional growth convergence; growth regression; kernel density estimators; Regionales Wachstum; Entwicklungskonvergenz; Regionale Entwicklung; Regionale Einkommensverteilung; Kolumbien